2016
DOI: 10.1371/journal.pone.0155082
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tolerance Induction in Experimental Autoimmune Encephalomyelitis with Candida utilis Expressing the Immunogenic MOG35-55 Peptide

Abstract: Multiple sclerosis (MS) is an autoimmune disease that attacks myelinated axons in the central nervous system. Induction of oral tolerance is a potent mechanism to prevent autoimmunity. The food yeast Candida utilis was used to test the therapeutic potential of oral tolerance induction in an animal model of human multiple sclerosis (MS). We constructed a C. utilis strain, which displays a fusion peptide composed of the encephalitogenic MOG35-55 peptide and the C. utilis Gas1 cell wall protein on its surface.By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Experimental autoimmune encephalomyelitis (EAE) is an animal model of human MS that has been used to study the effects of probiotic bacteria on CNS [11,12]. One of the safe and appropriate ways to modulate T cells in MS is to orally administer specific autoantigens [13,14]. Administration of Bifidobacteria or Lactobacteria probiotic strains to mice has been shown to increase Treg cells and tumor growth factor (TGF)-β levels and reduce the severity of EAE clinical symptoms, in parallel with improvement in the regeneration of myelin in the spinal cord compared to the control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is an animal model of human MS that has been used to study the effects of probiotic bacteria on CNS [11,12]. One of the safe and appropriate ways to modulate T cells in MS is to orally administer specific autoantigens [13,14]. Administration of Bifidobacteria or Lactobacteria probiotic strains to mice has been shown to increase Treg cells and tumor growth factor (TGF)-β levels and reduce the severity of EAE clinical symptoms, in parallel with improvement in the regeneration of myelin in the spinal cord compared to the control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Oral tolerance has an impact on the numbers and function of Treg cells, on the secretion of pro and anti-inflammatory cytokines and on Th-1/Th-2 effector cells (25). This observation led to attempts to regulate many autoimmune diseases by induction of mucosal tolerance to auto antigens (10,(26)(27)(28). We have previously shown that EAMG was prevented in rats by oral or nasal administration of AChR-derived recombinant fragments when treatment started prior immunization, moreover, ongoing disease was suppressed when mucosal tolerance treatment started at the acute or chronic phase of the disease (11,29).…”
Section: Discussionmentioning
confidence: 99%
“…Upon this, they are translocated to antigen-presenting cells of Peyer’s plaques or to other lymphoid tissue connected with the gastrointestinal tract [ 74 , 75 ]. The ingestion of engineered C. jadinii cells, carrying a myelin oligodendrocyte glycoprotein antigen on its surface, promoted tolerance to self-antigens in a mouse model of the autoimmune multiple sclerosis (MS) disease [ 76 ]. C. jadinii cells expressing the immunodominant MOG 35–55 epitope of a myelin protein on their surface, fused with the native fungal Gas1 cell wall protein, prevented the typical MS symptoms in this animal model [ 76 ].…”
Section: Emerging Biotechnological Applicationsmentioning
confidence: 99%